Professional development in early mathematics: effects of an intervention based on learning trajectories on teachers’ practices - Sarama, Julie; Clements, Douglas H.; Wolfe, Christopher B.; Spitler, Mary Elaine (NOMAD Nordic Studies in Mathematics Education, 2016)
We evaluated the effects of a research-based model for scaling up educational inter- ventions on teachers’ practices in preschool mathematics. The original participants were from 106 classrooms for 4-year-olds in two distal city districts serving low-resource communities, with 42 schools randomly assigned to one of three groups, of which the two treatment groups were the same throughout preschool (thus, there were 72 treatment classrooms). The intervention, a professional development program based on young children’s mathematical learning trajectories, had a substantial positive effect on teachers’ instructional practices, some of which mediated student outcomes. Teachers also demonstrated sustained levels of fidelity as long as six years after the end of the intervention. Notable is these teachers’ encouragement and support for discussions of mathematics and their use of formative assessment. Finally, teachers taught the curriculum with increasing fidelity over the following six years without support from the project.